Increasing hip and knee flexion during a drop-jump task reduces tibiofemoral shear and compressive forces: implications for ACL injury prevention training. Issue 24 (17th December 2017) - Tsai, Liang-Ching; Ko, Yi-An; Hammond, Kyle E.; Xerogeanes, John W.; Warren, Gordon L.; Powers, Christopher M.
ABSTRACT: Although most ACL injury prevention programmes encourage greater hip and knee flexion during landing, it remains unknown how this technique influences tibiofemoral joint forces. We examined whether a landing strategy utilising greater hip and knee flexion decreases tibiofemoral anterior shear and compression. Twelve healthy women (25.9 ± 3.5 years) performed a drop-jump task before and after a training session (10–15 min) that emphasised greater hip and knee flexion. Peak tibiofemoral anterior shear and compressive forces were calculated using an electromyography (EMG)-driven knee model that incorporated joint kinematics, EMG and participant-specific muscle volumes and patella tendon orientation measured using magnetic resonance imaging (MRI). Participants demonstrated a decrease in peak anterior tibial shear forces (11.1 ± 3.3 vs. 9.6 ± 2.7 N · kg −1 ; P  = 0.008) and peak tibiofemoral compressive forces (68.4 ± 7.6 vs. 62.0 ± 5.5 N · kg −1 ; P  = 0.015) post-training. The decreased peak anterior tibial shear was accompanied by a decrease in the quadriceps anterior shear force, while the decreased peak compressive force was accompanied by decreased ground reaction force and hamstring forces. Our data provide justification for injury prevention programmes that encourage greater hip and knee flexion during landing to reduce tibiofemoral joint loading.